Community Art and Health Promotion - Gridley, Heather (ANIMA Indonesian Psychological Journal, 2008)
Participating in ‘the arts’ has been variously claimed to offer individual, social, and com- munity health benefits. But what is meant by ‘the arts’? What is health, and what activities does ‘health promotion’ encompass? How can the impacts of arts initiatives be evaluated? This paper con- siders one particular community arts activity, group singing, that has potential for community health promotion. While there is evidence that singing is beneficial to the health and wellbeing of indivi- duals, less is known about the communal benefits of people coming together to sing as a group. This paper describes a study designed to investigate the mental health benefits of community-based sing- ing programs. A qualitative case example of a community choir is also presented to ‘give voice’ to the singers themselves. Berpartisipasi dalam “seni” dianggap melalui berbagai cara mampu memberikan manfaat bagi kesehatan individu, sosial, dan komunitas. Namun, apa yang dimaksud dengan “seni?” Apakah kesehatan itu, dan aktivitas apa yang diliput “promosi kesehatan?” Bagaimana dampak keterlibatan dalam seni dapat dievaluasi? Makalah ini menilai sebuah aktivitas seni komunitas yang khusus, ke- lompok nyanyi, yang potensial untuk promosi kesehatan komunitas. Sekalipun ada bukti bahwa ber- nyanyi bermanfaat untuk kesehatan dan kenyamanan individu, tak banyak yang diketahui tentang manfaat komunal dari orang-orang yang berkumpul untuk bernyanyi dalam kelompok. Makalah ini menjelaskan sebuah studi yang dirancang untuk meneliti manfaat kesehatan mental dari program bernyanyi yang berdasar komunitas. Sebuah contoh kasus kualitatif dari sebuah paduan suara komu- nitas juga dipresentasikan untuk “memberi suara” pada para penyanyinya sendiri.